Car l’homme est fait pour rechercher l’humain. Rileggere Eugène Minkowski - Di Gianfrancesco, Elvira; Giampà, Alessio (Il sogno della farfalla, 2016)
The current crisis in reductionist psychiatry has aroused new interest in psychopathology. The intent is to go beyond diagnosis based on set categories and tackle mental disease not only from a biological point of view. Within this perspective, Minkowski’s thought is particularly interesting. The article proceeds by highlighting Minkowski’s originality in his time and how he differs from Binswanger, who lived at the same time as Minkowski and is possibly more appreciated and undoubtedly better known. By providing a new interpretation of his best known works, the article develops and highlights the link between Bergson, Husserl and Minkowski on the one hand, and that between Jaspers, Heidegger and Binswanger on the other. Apart from Minkowski’s relation with philosophy, the Authors also evaluate his relation with psychology, the unconscious and psychoanalysis, language and existential analytics. The Authors, by making reference to Human Birth Theory by Massimo Fagioli, highlight some intuitions and the originality of the phenomenological analysis in Minkowski’s work, which have never been evidenced.